Impact of Bank Super App as Game Changer to Improve Funding Structure and Bank Wide Financial Performance: Case Study in BNI Super App (Wondr By BNI) - Ryan Hutomo Suhardi; Raden Aswin Rahadi (Eduvest - Journal of Universal Studies, 2025)
Based on performance in 2023, the share of Loans and Third-Party Funds from BNI decreased compared to 2022. In the profit and loss statement, BNI’s net interest income decreased by 0.1% (IDR 45.0 billion) compared to 2022. BNI’s Net Interest Margin (NIM) fell from 4.8% in 2022 to 4.6% in 2023. As a trusted financial institution, to address these business challenges, BNI launched a Super App in early July 2024. This research aims to analyze the correlation and evaluate the impact of the BNI Super App on BNI's funding structure and financial performance. This study employs both qualitative and quantitative research methods. The qualitative data analysis uses a content analysis approach, while the quantitative methods include correlation and paired samples t-test analyses. Data collection combines interviews and secondary data from BNI’s Annual Report and financial performance records. Based on the correlation results, Hypothesis 1 for CASA Ratio, Cost of Fund, NIM, and ROA is accepted. For impact results, Hypothesis 1 is accepted for Cost of Fund, NIM, and ROA, while it is rejected for CASA Ratio. There is a positive correlation between the BNI Super App—in terms of the number and volume of transactions—and CASA Ratio, NIM, and ROA, and a negative correlation with Cost of Funds. The results also show a significant impact after the launch of the Super App in reducing Cost of Fund and increasing NIM and ROA. However, the CASA Ratio has not yet increased significantly.